Driving improved burns care and patient outcomes through clinical registry data: A review of quality indicators in the Burns Registry of Australia and New Zealand. Issue 1 (February 2021) - Gong, Jennifer; Singer, Yvonne; Cleland, Heather; Wood, Fiona; Cameron, Peter; Tracy, Lincoln M.; Gabbe, Belinda J.
Highlights: Twenty-three quality indicators/data items are now collected in the registry. Four quality indicators were removed as they were not considered useful. Nine quality indicators/data items were revised. Eight new quality indicators/data items were added into the registry. Abstract: Background: In 2009, the Burns Registry of Australia and New Zealand (BRANZ) published a set of clinical quality indicators (QIs) to monitor performance, improve quality of care, and inform and change policy. With several years of data collected since the initial development of the indicators for burns, the BRANZ QI Working Party reviewed the clinical QIs for relevance and meaning, and considered new QIs that had not been collected previously. Method: Using published literature and expert opinion, the QI Working Party, consisting of multidisciplinary burn clinicians, reviewed the QIs for burn care to be included as routine data items in the BRANZ. Results: In July 2016, the list of clinical QIs in the BRANZ was updated to 23 QIs/data items, covering structure, process, and outcome measures. Four QIs were removed as they were not found to be useful, nine QIs/data items were revised, and eight new QIs/data items were added as they were considered to be clinically useful. Conclusion: This review outlines the changes made to the QIs collected by the BRANZ four years since their development and implementation. Ongoing refinement of the BRANZ QIs will ensure that high quality data is collected to drive improvements in clinical and patient outcomes.